FOREIGN DIRECT INVESTMENT IN SAUDI ARABIA - Ehmaidat, Abobaker; Jajuga, Krzysztof (The journal of contemporary issues in business and government, 2023)
Each nation strives to attract foreign direct investment (FDI) to boost its economy and close the saving-investment imbalance. Political considerations and falling oil prices had caused FDI flows to Saudi Arabia to steadily diminish, but commercial development and new initiatives beyond the petroleum and gas industry aided reversing the trend and pattern. Among 1983 and 2013, the strategies, rules, and growth of foreign direct investment in Saudi Arabia were studied using an analytical and descriptive strategy. The findings showed that economic factors strongly influenced FDI during the time period. About 60.3% of all foreign investments come from Saudi Arabia, which is beneficial for the host nation's economic growth. Short-term FDI has a negative impact on domestic investment capital, while long-term domestic capital investment has a negative impact on FDI. The Long-term non-oil GDP development, FDI inflows, and domestic capital expenditure are all favourably impacted by both the rise of the financial sector and exchange rates. The conclusions are crucial for Saudi policymakers to implement in order to lead and encourage local and foreign investments and stimulate economic growth in the nation. This research will focus on the foreign direct investment in Saudi Arabia, it will mainly deal with the relationship between the FDI and economic growth and how the FDI impacts the employment rate. This research also discusses the relationship between the GCC (Gulf Cooperation Council) countries and GDP (Gross Domestic Product) rate. The primary objective is to identify the variables affecting FDI in Saudi Arabia, the patterns, and trends of FDI and their relationship to GDP. A number of variables, including the relationship between inflow and outflow, the impact of inflow and outflow, and the sectoral composition of FDI based on the Kingdom of Saudi Arabia, are anticipated.